2005
DOI: 10.1161/01.cir.0000151610.98409.2f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Percutaneous Coronary Intervention on Coronary Microvascular Resistance Index

Abstract: Background-Coronary microvascular resistance during maximal hyperemia is generally assumed to be unaffected by percutaneous coronary interventions (PCIs). We assessed a velocity-based index of hyperemic microvascular resistance (h-MR v ) by using prototypes of a novel, dual-sensor (Doppler velocity and pressure)-equipped guidewire before and after PCI to test this hypothesis. Methods and Results-Aortic pressure, flow velocity (h-v), and pressure (h-P d ) distal to 24 coronary lesions were measured simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
102
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 44 publications
6
102
4
Order By: Relevance
“…In these territories, a possible coronary flow increase after PCI might be limited by responsive microvascular resistance increases. Currently, controversy exists about whether hyperemic microvascular resistance in the presence of functionally significant stenosis is equivalent to that after stenosis removal by PCI 9, 10, 26, 27, 28. Our results clearly demonstrated that microvascular resistance was affected by PCI, and its direction of change had an impact on CFR change and hyperemic coronary flow after successful PCI.…”
Section: Discussionmentioning
confidence: 50%
“…In these territories, a possible coronary flow increase after PCI might be limited by responsive microvascular resistance increases. Currently, controversy exists about whether hyperemic microvascular resistance in the presence of functionally significant stenosis is equivalent to that after stenosis removal by PCI 9, 10, 26, 27, 28. Our results clearly demonstrated that microvascular resistance was affected by PCI, and its direction of change had an impact on CFR change and hyperemic coronary flow after successful PCI.…”
Section: Discussionmentioning
confidence: 50%
“…It has been proposed that the presence of microvascular dysfunction is not an obstacle for making decisions based on FFR, provided that minimal and constant microvascular resistance with induced hyperemia is deemed to be nonreversible or consistent before and after revascularization 28, 29. However, several studies reported the evidence of serial changes in adenosine‐induced microvascular resistance before, after, and during follow‐up post‐PCI 13, 30, 31. van de Hoef et al also reported that identification of epicardial disease severity by FFR is partly obscured by microvascular resistance and that FFR increased with increasing hyperemic microvascular resistance to epicardial disease of equivalent severity 15.…”
Section: Discussionmentioning
confidence: 99%
“…A 0.014-in. dual-sensor guide wire (Volcano, Rancho Cordova, CA) with a Doppler sensor at the tip and a pressure sensor 3 cm proximal to the tip was advanced to a distal location in the interrogated coronary vessel to record intracoronary perfusion pressure (P d) and flow velocity (U) signals (20,25). Care was taken to place both sensors in a smooth vessel segment and to obtain an optimal and stable velocity signal according to recommended techniques for sensor-wire measurements (6).…”
Section: Methodsmentioning
confidence: 99%